2023
DOI: 10.3934/dcdss.2022103
|View full text |Cite
|
Sign up to set email alerts
|

Pattern formation of Brusselator in the reaction-diffusion system

Abstract: <p style='text-indent:20px;'>Time delay profoundly impacts reaction-diffusion systems, which has been considered in many areas, especially infectious diseases, neurodynamics, and chemistry. This paper aims to investigate the pattern dynamics of the reaction-diffusion model with time delay. We obtain the condition in which the system induced the Hopf bifurcation and Turing instability as the parameter of the diffusion term and time delay changed. Meanwhile, the amplitude equation of the reaction-diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Since the Lotka-Volterra model was proposed in the early twentieth century, some biological mechanisms were explained in the predator-prey system [12][13][14][15][16][17][18]. Chang et al researched the dynamics in the predator-prey system on complex networks and found that Turing instability caused by delay can generate spiral waves [19].…”
Section: Introductionmentioning
confidence: 99%
“…Since the Lotka-Volterra model was proposed in the early twentieth century, some biological mechanisms were explained in the predator-prey system [12][13][14][15][16][17][18]. Chang et al researched the dynamics in the predator-prey system on complex networks and found that Turing instability caused by delay can generate spiral waves [19].…”
Section: Introductionmentioning
confidence: 99%